Regulating online broadcast media against offensive materials in Malaysia - Islam, Md. Zahidul; Mokhtar, Khairil Azmin; Mohd Badrol Afandi, Nor Hafizah; Anzum, Rabeya (Indian Society for Education and Environment, 2021)
Nowadays, online broadcasting services such as, Hotstar, Hulu, Netflix, Iflix Pandora, Amazon Prime Video etc are very popular in Malaysia for original video contents. Due to the rapid growth of online broadcasting services in Malaysia, it is necessary to examine the legal and regulatory framework governing the contents of online broadcasting services. Objectives: The basic objective of this study is to scrutinize the efficacy and applicability of the Communications and Multimedia Act (1998) and other relevant laws of Malaysia in regulating online broadcasting services with special concentration on offensive materials and hate speeches. It also tries to identify the major weaknesses of the Malaysian Communications and Multimedia Commission (MCMC), the main regulatory body in dealing with this specific matter. Methods: Legal and doctrinal research methodology is applied in this study followed by an analytical approach. Relevant data are collected after analyzing both the primary and secondary legal sources. Finding: Findings of the study reveals that the contents of online broadcasting services do not frequently violate the relevant laws and regulations of Malaysia and sometimes their agreement with consumers are made in such a way as to avoid legal responsibility for the contents provided. Hence, it is recommended that the online broadcasting services and its contents should be made subject to a special legal framework by enacting new laws and introducing a special regulatory body.